IDPS PERFORMANCE ANALYSIS FOR MITIGATING SQL INJECTIONS AND SYN FLOOD ATTACKS - Sahren, Sahren; Dalimunthe, Ruri Ashari; Saputra, Herman; Kurnia Sirni, Dian Yudha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2023)
Abstract: Cyberattacks like SQL injection and syn flood attacks can threaten the information system security of an organisation or company. The Intrusion Detection and Prevention System (IDPS) is used as a solution to detect, prevent, and respond to these attacks. However, the effectiveness of IDPS in protecting information systems needs to be evaluated through performance analysis. IDPS performance analysis for mitigating SQL injection and syn flood attacks will use Suricata tools, where performance analysis will include evaluation of system accuracy and efficiency in detecting attacks, as well as the impact of the system on network or information system performance. By doing this performance analysis, it can be seen how effective the IDPS is in providing defences against such attacks. The results of the IDPS performance analysis can help an organisation or company select and implement the right IDPS according to the needs and conditions of the information system. Thus, organisations or companies can improve the security of their information systems from threatening cyber attacks. Keywords: IDPS; SQL_Injection; Suricata; Syn_Flood_Attack Abstrak: Serangan cyber seperti SQL Injection dan Syn Flood Attack dapat mengancam keamanan sistem informasi suatu organisasi atau perusahaan. Intrusion Detection and Prevention System (IDPS) digunakan sebagai solusi untuk mendeteksi, mencegah, dan merespons serangan-serangan ini. Namun, efektivitas IDPS dalam melindungi sistem informasi perlu dievaluasi melalui analisis performa. Analisis performa IDPS untuk mitigasi SQL Injection dan Syn Flood Attack ini akan menggunakan tools suricata dimana analisa performa akan meliputi evaluasi terhadap akurasi dan efisiensi sistem dalam mendeteksi serangan, serta dampak dari sistem terhadap kinerja jaringan atau sistem informasi. Dengan melakukan analisis performa ini, dapat diketahui seberapa efektif IDPS dalam memberikan perlindungan terhadap serangan-serangan tersebut. Hasil dari analisis performa IDPS dapat membantu organisasi atau perusahaan dalam memilih dan mengimplementasikan IDPS yang tepat sesuai dengan kebutuhan dan kondisi sistem informasi yang dimiliki. Dengan demikian, organisasi atau perusahaan dapat meningkatkan keamanan sistem informasi mereka dari serangan-serangan cyber yang mengancam. Kata kunci: IDPS; SQL_Injection; Suricata; Syn_Flood_Attack